Медиатехнологии в системе языковой подготовки иностранных студентов-медиков - Гейченко, Е. И.; Рагрина, Ж. М.; Гейченко, Катерина Іванівна; Рагріна, Жанна Михайлівна; Geychenko, E. I.; Ragrina, Z. M. (Могилев. ин-т МВД, 2016)
Статья посвящена вопросам роли медиаобразования в высшем учебном заведении, рассматриваются преимущества использования медиаобразовательных технологий в образовательном процессе, дается их классификация, систематизируются функции, которые они выполняют. The article deals with the role of media education in the higher educational establishments. The advantages of using media educational technologies in teaching and educational process are considered in this paper. Types and functions of the media educational technologies are described in this research.
Mediatechnologies in the system of the foreign medical students’ language training
Keywords: медиаобразование; медиатехнологии; медиаобразовательные технологии; media education; media technologies; media educational technologies